2015
DOI: 10.1590/1980-57642015dn93000002
|View full text |Cite|
|
Sign up to set email alerts
|

[RETRACTED ARTICLE] Culture as a variable in neuroscience and clinical neuropsychology

Abstract: Culture is a dynamic system of bidirectional influences among individuals and their environment, including psychological and biological processes, which facilitate adaptation and social interaction. One of the main challenges in clinical neuropsychology involves cognitive, behavioral and functional assessment of people with different sociocultural backgrounds. In this review essay, examining culture from a historical perspective to ethical issues in cross-cultural research, including the latest significant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 139 publications
(109 reference statements)
0
9
0
2
Order By: Relevance
“…Na perspectiva de Wajman, Bertolucci, Mansur e Gauthier (2015), a grande questão que se coloca é: "Como a neurociência cultural pode trabalhar dentro de uma estrutura que não dá primazia ao cérebro ou à cultura?" (Wajman, Bertolucci, & Gauthier, 2015). Uma resposta possível estáno rompimento das dicotomias: "natureza e cultura" ou "cérebro e cultura", ambas eixos de tensão da própria psicologia.…”
Section: Desafios Futuros Para a Neuropsicologia No Brasil E No Mundounclassified
“…Na perspectiva de Wajman, Bertolucci, Mansur e Gauthier (2015), a grande questão que se coloca é: "Como a neurociência cultural pode trabalhar dentro de uma estrutura que não dá primazia ao cérebro ou à cultura?" (Wajman, Bertolucci, & Gauthier, 2015). Uma resposta possível estáno rompimento das dicotomias: "natureza e cultura" ou "cérebro e cultura", ambas eixos de tensão da própria psicologia.…”
Section: Desafios Futuros Para a Neuropsicologia No Brasil E No Mundounclassified
“…There is a lack of research examining competencies necessary to assess REMs in neuropsychology (Wajman, et al, 2015). In fact, little is known about multicultural assessment practices within neuropsychology, and Elbulok-Characape et al (2014) concluded that only one previous study investigated neuropsychological assessment practices with REMs (e.g., Echemendia et al, 1997).…”
Section: Multicultural Competence and Neuropsychologymentioning
confidence: 99%
“…Multicultural competence defines the awareness, knowledge, and skills needed to provide psychological services to individuals from diverse backgrounds, while neuropsychology is a specialty within professional psychology that applies assessment practices to study brainbehavior relationships (Bodin, Roper, O'Toole, & Haines, 2015;Jurado & Peuyo, 2012;Nell, 2000;. Despite the diversification of the United States and those seeking neuropsychological services, REM trainees and practitioners remain underrepresented (Cope et al, 2016;Rivera Mindt et al, 2010;Wajman et al, 2015). This discrepancy highlights the importance of competencies for working with diverse groups.…”
Section: Multicultural Competence and Neuropsychological Assessmentmentioning
confidence: 99%
See 2 more Smart Citations